Distribution of Bowen ratio over the north Indian Ocean - RAO, GRL; RAO, MV; PRASAD, PH; REDDY, KG (MAUSAM, 1986)
The monthly averages of Bowen ratio over the North Indian Ocean have been computed. Three typical situations in the months of January, May and September are taken for the present study. Month to month differences in the Bowen ratio over the study region are found significant and discussed in relation to the monsoonal behaviour of summer as well as winter.